A retrospective study of panoramic radiographs for zygomatic air cell defect in children - Srikanth H Srivathsa; Suchetha N Malleshi; Karthikeya Patil; Mahima V Guledgud (Wolters Kluwer Medknow Publications, 2014)
Background and Aim: The aim was to determine the prevalence of zygomatic air cell defect (ZACD) among children of Indian origin and also to determine the dominant form of ZACD. Materials and Methods: One thousand six hundred and eighty-eight routine panoramic radiographs of subjects between 7 and 18 years, processed between January 2006 and January 2009 were screened, recorded and analyzed for ZACD. Results: Of the 1688 panoramic radiographs examined, 768 were of males and 920 of females. The radiographs were divided into two groups, Group I comprising of subjects in the age 7-12 years and other Group II in the age range 13-18 years. ZACD was found in 50 subjects, accounting for prevalence of 2.96%. Other occurrences found were unilateral 38 cases, bilateral 12, unilocular 20 and multilocular 42 respectively. Conclusion: This study described the prevalence and characteristics of ZACD among selected Indian children. It is essential to know and determine this variant of normal anatomy and differentiate it from pathologies.